15th century Renaissance in full bloom - Hribar, Mariano Nicora; RCS Editori Rizzoli Corriere della Sera. (New York RCS Sansoni Editore Spa-Firenze, 1990)
Presents key masterpieces of artists during the flowering of the Renaissace in 15th century Italy like Botticelli, Angelico, Codussi, Lambardo, Bellinis Carpaccio Andrea del Castagno, etc.
Based on the book Storia de'll Arte Italliano by Guilio Carlo Argan.
VHS.
Keywords: Art -- Italy; Art, Renaissance; Art -- 15th century